Distribution of histaminergic neurons and their modulatory effects on oscillatory activity in the olfactory center of the terrestrial slug Limax. Issue 1 (16th July 2015) - Matsuo, Ryota; Fukata, Rena; Kumagai, Moeko; Kobayashi, Asuka; Kobayashi, Suguru; Matsuo, Yuko
ABSTRACT: Terrestrial mollusks can form an odor aversion memory following the simultaneous presentation of a food odor and an aversive stimulus. The local field potential oscillation recorded on the surface of the procerebrum (PC; the higher olfactory center) exhibits a frequency change in response to the detection of a learned odor; such a change is thus considered to reflect the internal state of the brain during memory recall. Thus far, dopamine and serotonin have been demonstrated to change the oscillatory frequency. Other monoamines, however, have not yet been studied. In the present study, we investigated the possible involvement of histamine (HA). Immunohistochemical staining of HA and in situ hybridization against histidine decarboxylase revealed the location of the cell bodies of HAergic neurons in all ganglia of the brain. The majority of them were located at the medial aspect of the pedal ganglia, and the cerebral ganglia also contained numerous HAergic neurons in their posterior regions. The neuropil layers of the PC received HAergic innervation from the neurons in the cerebral ganglion, as well as from a few neurons located in the dorsomedial part of the cell mass layer of the PC. The HAergic fibers, however, innervated spatially limited regions of the PC, and seemed to affect a small fraction of the PC neurons. HA exerted accelerating effects on the LFP oscillation in a dose‐dependent manner, and this effect was suppressed by an H2 blocker, cimetidine. Our results support the involvement of HA in the functioning of the PC. J. Comp. Neurol. 524:119–135, 2016. © 2015 Wiley Periodicals, Inc. Abstract : Filed potential oscillation in the higher olfactory center is thought to reflect higher olfactory functioning in terrestrial mollusks. The authors show histaminergic projections into the olfactory center from internal areas of the brain, and a potent effect of histamine on the field potential oscillation in the terrestrial slug Limax .